2003
DOI: 10.1046/j.1471-4159.2003.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of P2X3, P2Y1 and P2Y4 receptors in cultured HEK293‐hP2X3 cells and their inhibition by ethanol and trichloroethanol

Abstract: Membrane currents and changes in the intracellular Ca ] i was observed after the slow superfusion of ATP, ADPb-S and UTP; a,b-meATP was ineffective. These data, in conjunction with results obtained by using the P2 receptor antagonists TNP-ATP, PPADS and MRS2179 indicate that the current response to a,b-meATP is due to P2X 3 receptor activation, while the ATP-induced rise in [Ca 2+ ] i is evoked by P2Y 1 and P2Y 4 receptor activation. TCE depressed the a,b-meATP current in a manner compatible with a non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 45 publications
7
48
1
Order By: Relevance
“…Because GDP-␤-S is known to inhibit G-protein-mediated second-messenger mechanisms (Sternweis and Pang, 1990) of, for example, P2Y receptors (Ralevic and Burnstock, 1998), it has been suggested that endogenous P2Y receptors of HEK293 cells may negatively interact with the exogenous hP2X 3 receptor (Fischer et al, 2003). In the present study, UTP may exert both a P2Y 4 receptor-mediated depression and a hitherto unknown facilitation of P2X 3 receptors.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Because GDP-␤-S is known to inhibit G-protein-mediated second-messenger mechanisms (Sternweis and Pang, 1990) of, for example, P2Y receptors (Ralevic and Burnstock, 1998), it has been suggested that endogenous P2Y receptors of HEK293 cells may negatively interact with the exogenous hP2X 3 receptor (Fischer et al, 2003). In the present study, UTP may exert both a P2Y 4 receptor-mediated depression and a hitherto unknown facilitation of P2X 3 receptors.…”
Section: Resultsmentioning
confidence: 63%
“…Potentiation by UTP of the ␣,␤-meATP current amplitude in HEK293-hP2X 3 cells and interaction with protein kinase C inhibitors Although in HEK293-hP2X 3 cells, ATP, ␣,␤-meATP, and UTP caused, at a holding potential of Ϫ60 mV, inward currents, the threshold concentrations of ATP and ␣,␤-meATP were Ͼ0.3 M, whereas the threshold concentration of UTP was considerably higher (Ͼ10 M) (Fischer et al, 2003). In accordance with these results, UTP (3 M) did not evoke a current response by itself and also failed to alter the effect of ␣,␤-meATP (3 M; 1 s superfusion time) (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…HEK293 cells express metabotropic P2Y receptors capable of increasing the concentration of intracellular Ca 2ϩ ([Ca 2ϩ ] i ) by mobilizing internal Ca 2ϩ stores in a GTP-dependent manner (76,77). We used a HEK293 cell line with stable expression of the genetically encoded Ca 2ϩ sensor, GCaMP5G (78), to determine whether activation of P2Y receptors by ATP (6 mM) is an unintended consequence of using high agonist concentrations to measure Pf %.…”
Section: Resultsmentioning
confidence: 99%